Overcrowding in correctional centres and community reintegration of offenders: implications for correctional officials of a facility in North West Province, South Africa - Legodi, Refiloe; Dube, Misheck (Penerbit Universiti Kebangsaan Malaysia, 2023)
As part of the rehabilitation of offenders, South Africa has emerged as one of the countries in the world that uses programmed reintegration of offenders into the communities. However, overcrowding in correctional facilities has implications for correctional officials' work in the reintegration of offender’s programmes. This paper discusses overcrowding at Rooigrond Correctional Centre in the North West Province in South Africa and the implications it has for the work of correctional officials at the facility. The study applied a qualitative approach and a descriptive research design to capture the experiences of the correctional officials on the implication of overcrowding on the reintegration of offenders. Using the quota sampling method and semi-structured face-to-face interviews, ten correctional officials of different ranks participated in the study. Thematic data analysis employed showed that overcrowding in a correctional facility affects negatively the reintegration programmes at Rooigrond Correctional Centre making the rehabilitation process difficult and less effective. To enable and facilitate the successful reintegration of offenders into the communities, the study makes significant recommendations for consideration by correctional officials.